IMPLEENTATION OF STANDARD OPERATIONAL PROCEDURES AT SYAHBANDAR FISHING PORT OF BUNGUS AT WEST SUMATERA - Ameliawati Ameliawati; Pareng Rengi; Jonny Zain (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
Abstrak Syahbandar is the forefront of a fishing port in direct service to fishermen. In carrying out its duties, syahbandar must have guidance and reference so that the activities carried out can be run properly as expected, SOP role to facilitate the activity of an activity, it is necessary research about the application of SOP in syahbandar fishery port. This study aims to determine whetherKesyahbandaran in Bungus Ocean Fishery Port has implemented Standard Operating Procedures (SOP) as a reference in carrying out its duties. The research was conducted at Bungus Ocean Fishing Port. This research uses survey method that is doing direct observation in the field. The result of research shows that the absorption of soup in syahbandar pps bungus has not fully applied maximally. This is influenced by some fundamental things. This is caused by the lack of socialization between the officers of syahbandar and the fishermen about the soup in syahbandar, the lack of qualified personnel in the field of fishery, the knowledge of fishermen about the technology to make the arrangement of shti and logbook not running properly, the length of the extension of the extension of the SIPI, the lack of facilities and infrastructure for the activities and smooth tasks kesyahbandaran especially internet network access is still often problematic. Keywords: Standard operational procedures, Syahbandar, Fishery Port,